Structure and Expression of Bud Dormancy-Associated MADS-Box Genes (DAM) in European Plum - Quesada-Traver, Carles; Guerrero, Brenda Ivette; Badenes, María Luisa; Rodrigo, Javier; Ríos, Gabino; Lloret, Alba (Frontiers in Plant Science, 2020)
Bud dormancy in temperate perennials ensures the survival of growing meristems under the harsh environmental conditions of autumn and winter, and facilitates an optimal growth and development resumption in the spring. Although the molecular pathways controlling the dormancy process are still unclear, DORMANCY-ASSOCIATED MADS-BOX genes (DAM) have emerged as key regulators of the dormancy cycle in different species. In the present study, we have characterized the orthologs of DAM genes in European plum (Prunus domestica L.). Their expression patterns together with sequence similarities are consistent with a role of PdoDAMs in dormancy maintenance mechanisms in European plum. Furthermore, other genes related to dormancy, flowering and stress response have been identified in order to obtain a molecular framework of these three different processes taking place within the dormant flower bud in this species. This research provides a set of candidate genes to be genetically modified in future research, in order to better understand dormancy regulation in perennial species.